Pengaruh Implementasi Pembelajaran Berbasis AR Model Pembelajaran PjBL terhadap Keterampilan Bertanya dan Berpikir Kritis Siswa Materi Sistem Reproduksi Kelas XI SMA Negeri 14 Samarinda - Ramadhani, Salsabila Royani Putri; Masitah, Masitah; Herliani, Herliani; Rambitan, Vandalita Magdalena Maria (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to test the effectiveness of the use of Augmented Reality (AR) technology in the Project Based Learning (PjBL) model on improving students' questioning and critical thinking skills. The method used is a quasi-experimental method with a non-equivalent control group design. The subjects of the study were students of grade XI SMAN 14 Samarinda who were divided into an experimental class and a control class, each consisting of 20 students. The research instruments used were essay tests, observation sheets, and documentation. The data analysis techniques used were descriptive statistics (mean and standard deviation), N-Gain test, t-test (Independent Sample T-Test), and Normality & Homogeneity test using SPSS 25 for Windows. The results of the analysis showed a more significant increase in skills in the experimental class compared to the control class. The N-Gain value of the experimental class' questioning skills was 0.46 (moderate category), while the control class was 0.21 (low). For critical thinking, the experimental class obtained 0.51 (moderate), higher than the control class 0.33 (moderate). These findings indicate that AR integration in PjBL effectively improves questioning and critical thinking skills, and contributes to 21st century learning innovation.